The joint impact of working capital and platform-economy on firm profitability: The case of e-business model in transition country; Journal of Open Innovation: Technology, Market, and Complexity; Vol. 9, iss. 2 - Vukovic D. Darko; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Spitsin V. V. Vladislav Vladimirovich; Gribanova E. B. Ekaterina Borisovna (2023, 2023)
Title screen